Pengaruh Electronic Word Of Mouth, Brand Image, dan Perceived Price Terhadap Buying Decision (Studi Pada Pengguna Sepatu Compass di Kota Medan) - Rivaldo Sinaga, Eko Samuel; Harahap, Kartini; Siregar, Onan Marakali (Universitas Serambi Mekkah, 2024)
Consumer buying decisions for shoe products are supported by high electronic word of mouth on social media. The more popular a shoe brand is, the better the brand image of the shoe will be for consumers. Perceived price or perception of price that matches quality will also be a consumer consideration. This study aims to analyze how electronic word of mouth, brand image, and perceived price influence buying decisions of Compass shoe users in Medan City. The influence of electronic word of mouth, brand image, and perceived price will be analyzed partially and simultaneously on buying decisions. The form of research used is quantitative with an associative approach. The population in this study is Compass shoe users in Medan City. Sampling was carried out through purposive sampling technique and used 100 respondents as samples. Primary data used in this study were obtained by distributing questionnaires directly and secondary data were obtained through literature studies. The analysis methods used are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that electronic word of mouth (X1), brand image (X2), and perceived price (X3) have a significant effect both partially and simultaneously on the buying decision of Compass shoes in Medan City (Y). The coefficient of determination test shows that there is a very close relationship between electronic word of mouth, brand image, perceived price on buying decisions with an R value of 0.897. Through the adjusted R square value, it is also known that the electronic word of mouth, brand image, and perceived price variables contribute 79.8% to the buying decision variable while the remaining 20.2% is influenced by variables outside this study.